63 Short term results of intra-vitreal bevacizumab for the treatment of macular edema secondary to retinal vein occlusion - Thapa, R; Paudyal, G (Nepalese Journal of Ophthalmology, 2013)
Introduction: Macular edema (ME) is the leading cause of visual impairment in retinal vein occlusion (RVO). Objective: To evaluate the efficacy and safety of intravitreal bevacizumab (Avastin; Genentech) on ME secondary to RVO. Materials and methods: A prospective, interventional study was conducted among patients with ME due to RVO from June 2008 to February 2010. Intravitreal bevacizumab (1.25 mg/0.05 ml) was given at 4 to 6 weekly intervals until the ME subsided. Complete ophthalmic evaluation and measurement of central retinal thickness (CRT) by optical coherence tomography (OCT) were performed at baseline and follow up visits. Results: Thirty four eyes (18 CRVO and 16 BRVO) were included in the study. The mean duration of visual symptoms and follow up period were 5.1 months (range 0.3 - 24 months) and 7.5 ± 4.8 months respectively. In CRVO, the CRT improved from 652 ± 206 ?m at the baseline to 257 ± 132 ?m (p < 0.0001) at the final follow up, and in BRVO, the CRT improved from 540 ±197 ?m to 219 ± 135 ?m (p < 0.0001). The improvement in BCVA was significant at each follow up interval for BRVO; in CRVO, there was only a significant improvement between the baseline and the 6 weeks’ follow up. BCVA was improved in 75 % cases of BRVO and in 61.6 % in CRVO at the final follow up. There were no ocular or systemic adverse effects. Conclusion: Intravitreal bevacizumab is an effective and safe drug for reducing ME and improving visual acuity secondary to RVO in the short term follow up. Nepal J Ophthalmol 2013; 5(9):63-68 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7824